Pemberian Buah Pepaya Segar terhadap Penurunan Tekanan Darah Sistolik dan Diastolik pada Lansia Penderita Hipertensi - Sensiana, Maria Francona; Isnawati, Muflihah; Setiadi, Yuwono (Poltekkes Kemenkes Semarang, 2013)
Background : Hypertension is a disease with high morbidity and mortality in elderly people. High potassium food such as papaya is a potential sources for decreasing systolic and diastolic blood pressure.Objective : To investigate the effect of fresh papaya on lowering systolic and diastolic blood pressure in elderly patients with hypertension.Method : This study was an experimental research with pre and post test control group design. Number of elderly involved in this study were 20 persons, divided in two groups, firstly , 10 person in treatment group received 350 gr/ day papaya (containing 899,5 mg of potassium) for 7 days. Second group was a control group. Systolic and diatolic blood pressure were measured before and after treatment (in tfe first and 7th day) Data were analyzed using Paired t-test,.Results : There were differences in systolic (p1 = 0.028) and diastolic (p2 = 0.022) blood pressure between the treatment and control groups In the treatment group there was a decrease in systolic and diastolic blood pressure (p2 = 0.014) after given fresh papaya and after treatment (p=0,014)Conclusion : Consuming 350 gr/day of fresh papaya could decrease systolic and diastolic blood pressure in hypertensive elderly subject.